Generalized Transversal Lightlike Submanifolds of Indefinite Sasakian Manifolds - Yaning Wang; Ximin Liu (International Journal of Mathematics and Mathematical Sciences)
We introduce and study generalized transversal lightlike submanifold of indefinite Sasakian manifolds which includes radical and transversal lightlike submanifolds of indefinite Sasakian manifolds as its trivial subcases. A characteristic theorem and a classification theorem of generalized transversal lightlike submanifolds are obtained.